2010
DOI: 10.1007/s00428-010-0885-9
|View full text |Cite
|
Sign up to set email alerts
|

Localized intrapancreatic malignant mesothelioma: a rare entity that may be confused with other pancreatic neoplasms

Abstract: Malignant mesothelioma usually presents with diffuse involvement of the pleura or peritoneum. Circumscribed or localized malignant mesothelioma has been described in these locations, as well as the viscera, in which case it may cause diagnostic confusion with other, more common entities. Herein, we describe the first well-documented case of primary intrapancreatic malignant mesothelioma in the English literature. The patient was an otherwise healthy 39-year-old woman who presented with a symptomatic mass in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
5
14
2
Order By: Relevance
“…In the English literature only very few cases have been reported that occurred in lung, 5 testis, 6 ovary, 6 liver, 3 and pancreas. 4 In the present report, we describe an epithelioid malignant mesothelioma arising inside the splenic parenchyma of a 48-year-old man without a history of asbestos exposure. The tumor was incidentally detected as an intrasplenic nodule without any other lesions in the pleura and peritoneum.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In the English literature only very few cases have been reported that occurred in lung, 5 testis, 6 ovary, 6 liver, 3 and pancreas. 4 In the present report, we describe an epithelioid malignant mesothelioma arising inside the splenic parenchyma of a 48-year-old man without a history of asbestos exposure. The tumor was incidentally detected as an intrasplenic nodule without any other lesions in the pleura and peritoneum.…”
Section: Discussionmentioning
confidence: 82%
“…In the English literature only very few cases have been reported that occurred in lung, 5 testis, 6 ovary, 6 liver, 3 and pancreas. 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant mesothelioma often presents with diffuse involvement of the serous membranes, localized malignant mesotheliomas are extremely rare solitary circumscribed nodular tumors ( 4 ). Only very few cases have been reported that presented in ovary ( 5 ), liver ( 6 ), pancreatic ( 7 ) and lung ( 8 ). Diagnosing intrapulmonary malignant mesothelioma on the basis of clinical findings alone is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of pancreatic mesothelioma is different depending on the pathological type and stage. Rosanny et al 3 reported a case of intra-pancreatic epithelioid malignant mesothelioma. Follow-up revealed no evidence of residual or recurrent disease 32 months after pancreatoduodenectomy without adjuvant radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%